1212-Molybdo-Cuprates; effect of oxygenation in the structure, properties and electronic states. Issue 1655 (6th May 2014) - Marik, Sourav; Dos santos-Garcia, A. J.; Labrugere, Christine; Morán, Emilio; Toulemonde, Olivier; Alario-Franco, M. A.
ABSTRACT: The influence of oxygenation in the magnetism, superconductivity and electronic states for the Mo0.3 Cu0.7 Sr2 RECu2 Oy (RE = Y, Er and Tm) compounds are discussed here. The magnetic measurements on the as-prepared (AP) samples suggest the existence of short-range magnetic correlations due to the presence of the paramagnetic Mo V cations in the copper chain site. On the other hand, all the oxygenated samples are not magnetic but superconducting. The high pressure oxygenated sample shows the highest superconducting transition temperature of TC = 84 K. The influence of oxygenation in the electronic states for the Mo0.3 Cu0.7 Sr2 YCu2 Oy system associated with an oxidation reaction leading from a non-superconducting to a superconducting state has also been investigated by means of X-ray photoelectron spectroscopy (XPS). XPS measurements show the predominance of the Mo V oxidation state over the Mo VI one in the AP material; annealing under flowing oxygen enhances both the Mo VI and Cu II amounts. A detailed study of the electronic states for the Mo0.3 Cu0.7 Sr2 YCu2 Oy samples has been performed and is also discussed.